Identification of two distinct human immunodeficiency virus type 1 Vif determinants critical for interactions with human APOBEC3G and APOBEC3F. - Russell, R; Pathak, V (2007)
Human cytidine deaminases APOBEC3G (A3G) and APOBEC3F (A3F) inhibit replication of Vif-deficient human immunodeficiency virus type 1 (HIV-1). HIV-1 Vif overcomes these host restriction factors by binding to them and inducing their proteasomal degradation. The Vif-A3G and Vif-A3F interactions are attractive targets for antiviral drug development because inhibiting the interactions could allow the host defense mechanism to control HIV-1 replication. It was recently reported that the Vif amino acids D(14)RMR(17) are important for functional interaction and degradation of the previously identified Vif-resistant mutant of A3G (D128K-A3G). However, the Vif determinants important for functional interaction with A3G and A3F have not been fully characterized. To identify these determinants, we performed an extensive mutational analysis of HIV-1 Vif. Our analysis revealed two distinct Vif determinants, amino acids Y(40)RHHY(44) and D(14)RMR(17), which are essential for binding to A3G and A3F, respectively. Interestingly, mutation of the A3G-binding region increased Vif's ability to suppress A3F. Vif binding to D128K-A3G was also dependent on the Y(40)RHHY(44) region but not the D(14)RMR(17) region. Consistent with previous observations, subsequent neutralization of the D128K-A3G antiviral activity required substitution of Vif determinant D(14)RMR(17) with SEMQ, similar to the SERQ amino acids in simian immunodeficiency virus SIV(AGM) Vif, which is capable of neutralizing D128K-A3G. These studies are the first to clearly identify two distinct regions of Vif that are critical for independent interactions with A3G and A3F. Pharmacological interference with the Vif-A3G or Vif-A3F interactions could result in potent inhibition of HIV-1 replication by the APOBEC3 proteins.